KALIMAT NEGATIF DALAM FILM THE FAULT IN OUR STARS OLEH JOHN GREEN - Wongkar, Grethy Gabriel (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT   This research entitled Negative Sentences in the Film The Fault in Our Stars by John Green. The objectives of this research are to identify, to collect and to analyze the negative forms of negative sentences. This research used descriptive method. The writer collected the data of negative sentences from the subtitles in the film The Fault in Our Stars by John Green. After collecting the data, the writer analyzed forms of negative sentences and found out the negative sentences in this film that are mostly used by using the theories of Aarts and Aarts (1982) and Azar (1993). The result of this research shows that there are 215 negative sentences found in the film The Fault in Our Stars by John Green. The writer only analyzed 150 data. The forms of negative sentences consist of negative sentences which are formed of do (43), not (37), auxiliary verb and not (24), negative prefixes (17), negative interrogatives (12), no (5), negative sentences contain have (4), question tag (2), never, rarely, seldom, hardly (ever), scarcely (ever), barely (ever) (3), negative sentences contain do and let’s (1), negative sentences contain do and be (1), negative sentences contain have and do (1). Negative sentences that contains daren’t, usedn’t, needn’t (0), negative suffixes (0) are not found in this research. Negative Sentence which is mostly used in this film is negative sentence formed of do with 43 data.   KEYWORDS: Negative Sentences, Film The Fault in Our Stars, Descriptive Analysis